Effect of obesity on Covid-19 anxiety and role of self-esteem on women: Obestiy and Covid-19 anxiety - Altunal, Çetin; Borku Uysal, Betül; İslamoğlu, Mehmet Sami (Progress in Nutrition, 2023)
In this prospective study, it was aimed to evaluate effects of obesity on Covid-19 anxiety and role of self-esteem on women. Obese (n = 184) and non-obese women (n = 219) who applied to our clinic in the first six months of 2020 were included in the study. The women included in the study were divided into two groups as having Body Mass Index (BMI) 30 or more obese according to the WHO criteria. Demographic information form, the Rosenberg Self-Esteem Scale and the Covid-19 Anxiety Scale was used for data collection. Most of the obese participants were housewives, and the difference was statistically significant (p